Evaluasi Pelaksanaan Pembinaan Industri Kecil Oleh Dinas Koperasi Usaha Kecil Menengah Dan Perdagangan Kabupaten Sekadau - Yulita Oktavia; Netty Herawati; Lina Sunyata (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to evaluate how well the Sekadau Regency Office of Cooperatives, Small and Medium Enterprises, and Trade (OCSMET) has implemented coaching for small industries to improve the competitiveness and capabilities of small business owners. To find out if the coaching activities meet the needs of business owners, how resources for coaching are available, how the coaching is carried out, and what outcomes and impacts result from the coaching activities by the Office of Cooperatives, SMEs, and Trade of Sekadau Regency, data was gathered through interviews with government officer/Civil Servant officials at OCSMET Sekadau Regency and small industry entrepreneurs who took part in the coaching. This data was analyzed using the CIPP Method (Context, Input, Process, and Product). The findings showed that small industry participants need this coaching program. To achieve better results in the long run, it is recommended that OCSMET enhance collaboration with other agencies and institutions, strengthen the training budget, increase the number and facilities of industrial development staff, and create a database of small industry business owners. Additionally,OCSMET should establish a sustainable coaching system after training.